A RESEARCH ON THE RELATİONSHİP OF CHARİSMATİC LEADERSHİP BEHAVİORS OF AGRİCULTURAL COOPERATİVE MANAGERS WİTH COOPERATİON OF SHAREHODERS AND PERFORMANCE-SATİSFACTİONS (Third Sector Social Economic Review, 2013)
In this study, the effects of charismatic leadership qualities of managers in agricultural cooperatives were investigated. A model representing the relationship between the variables was established and the hypotheses were tested. The validity and reliability analyses for the model were performed, finding that these criteria were met. The research data was collected from 155 shareholder of ÇUKOBIRLIK operating in the eastern Mediterranean via a questionnaire. The data was analyzed by a partial least square structural equation modeling method (PLS-SEM). The analysis results demonstrated that the charismatic leadership of the cooperative managers impacted the sharehoders' commitments to each other, the cooperation between shareholders, and the satisfaction expressed through shareholder performance. It was found that the commitment of shareholders to each other affected cooperation amongst themselves significantly. In addition, the research model explained the high level of shareholder performance-satisfaction as well as cooperation between the shareholders variables.
Keywords: Agricultural cooperatives; Charismatic leadership; shareholder performance – satisfaction; cooperation; Çukobirlik